TINJAUAN EFEKTIFITAS JALAN DAN SALURAN DRAINASE DI JALAN H.S. RONGGOWALUYO, TELUKJAMBE TIMUR, KARAWANG - Putri, Anggi Safira; Pura, Margo Hadi (Hukum dan Masyarakat Madani, 2021)
Jalan H.S. Ronggowaluyo in Kab. Karawang is one of the streets that is narrow but densely populated and also buildings in the form of houses, shops, and educational buildings. However, the road conditions and drainage on this road is still not optimal. A bad drainage system can cause water to overflow until there could be a flooding on the road. This study uses a juridical normative and empirical juridical approach. The role of the government and society is needed in improving the road conditions and the drainage systems. That way, it can be ascertained that the traffic will be orderly, and the road conditions will be clean and comfortable if motorized vehicle drivers passing by, it and also for the people who live around the H.S. Ronggowaluyo.
Keywords: Drainage; Effectivity; Road.